Penerapan Teknologi Tepat Guna Pada Masyarakat Kayubulan Kabupaten Gorontalo Melalui Pengolahan Limbah Organik, Anorganik dan Eceng Gondok - Nita Suleman; Yuszda K Salimi; Netty I Ischak; Jhodi Pratama Djalil (Damhil: Jurnal Pengabdian kepada Masyarakat, 2022)
The problem of hyacinths in the Limboto lake of Gorontalo Regency has not yet been resolved, causing silting of the lake. Organic and inorganic waste also aggravated the silting. The application of appropriate technology to the Kayubulan community aims to educate the public through organic, inorganic, and hyacinth waste treatment technology. The stages of activities are in the form of community education, consultation, diffusion of science and technology, training, mediation, science and technology simulation, substitution of science and technology, advocacy. The results of this activity provide an understanding to the community about the use of hyacinth, plastic waste, garbage and livestock manure intop roduk in the form of organic solid fertilizer, liquid fertilizer, briquettes, bioethanol, and handicrafts. This activity has a positive impact on increasing the knowledge and skills of the target partners of the young people of the Kayubulan community.